1993
DOI: 10.1182/blood.v81.9.2263.bloodjournal8192263
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant immunotoxin therapy with anti-B4-blocked ricin after autologous bone marrow transplantation for patients with B-cell non- Hodgkin's lymphoma

Abstract: Anti-B-blocked ricin (anti-B4-bR) combines the specificity of the anti- B4 (CD19) monoclonal antibody with the protein toxin “blocked ricin.” In blocked ricin, affinity ligands are attached to the ricin B-chain to attenuate its lectin binding capacity. In a phase I trial, Anti-B4-bR was administered by 7-day continuous infusion to 12 patients in complete remission after autologous bone marrow transplantation (ABMT) for relapsed B-cell non-Hodgkin's lymphoma (NHL). Patients were treated at 20, 40, and 50 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The increasing intensity of high‐dose systemic cytarabine and intrathecal therapy had led to a marked decline in the risk of CNS relapse without the use of radiotherapy (Bowman et al , 1996; Atra et al , 1998, 2000). High‐dose chemo/radiotherapy and stem cell rescue with or without monoclonal antibodies or immunotoxins may cure some patients, although the overall results remain disappointing (Grossbard et al , 1993; Philip et al , 1993). In addition to the stage of disease at diagnosis, patients with bulky abdominal lymphoma, CNS disease or high lactate dehydrogenase (LDH) level at diagnosis have a less favourable outcome (Reiter et al , 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing intensity of high‐dose systemic cytarabine and intrathecal therapy had led to a marked decline in the risk of CNS relapse without the use of radiotherapy (Bowman et al , 1996; Atra et al , 1998, 2000). High‐dose chemo/radiotherapy and stem cell rescue with or without monoclonal antibodies or immunotoxins may cure some patients, although the overall results remain disappointing (Grossbard et al , 1993; Philip et al , 1993). In addition to the stage of disease at diagnosis, patients with bulky abdominal lymphoma, CNS disease or high lactate dehydrogenase (LDH) level at diagnosis have a less favourable outcome (Reiter et al , 1995).…”
Section: Discussionmentioning
confidence: 99%
“…High‐dose systemic cytarabine and etoposide may salvage some relapsed or unresponsive cases (Gentet et al , 1990). High‐dose chemo/radiotherapy with stem cell rescue may cure some patients, although its role is difficult to assess because of small numbers (Philip et al , 1993) and the value of adjuvant therapy using immunotoxins or monoclonal antibodies remains to be clarified (Grossbard et al , 1993). In this study, we reviewed all patients who had primary resistant disease or relapsed after first‐line therapy with the United Kingdom Children Cancer Study Group (UKCCSG) 9003/9002 protocols to assess their curability after more intensive chemotherapy with or without megatherapy and stem cell rescue.…”
mentioning
confidence: 99%
“…Unconjugated mouse anti-CD19 antibodies (CLB-CD19) were used to treat low-grade non-Hodgkin’s lymphoma [ 29 ]. An immunotoxin (Anti-B4-bR) targeting CD19 was used against relapsed B-cell non-Hodgkin’s lymphoma (NHL) [ 30 ] and the CD19 and CD3 binding bispecific T-cell engager (Blinatumomab) was used to eliminate refractory B-precursor acute lymphoblastic leukemia [ 31 ]. All studies revealed efficacy in cancer elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Although anti‐B4‐bR could be administered safely to patients by 7 d continuous infusion, antigen excess remained a difficult problem to overcome when treating patients with bulky relapsed tumours. Therefore, we conducted another clinical trial using anti‐B4‐bR as adjuvant therapy in patients with B‐cell non‐Hodgkin's lymphoma who were in clinical complete remission following autologous bone marrow transplantation (ABMT) ( Grossbard et al , 1993a ). The maximum tolerated dose in that study was 40 μg/kg/d for 7 d by continuous intravenous infusion, achieving serum levels of 1.1–2.6 n M .…”
Section: Discussionmentioning
confidence: 99%